Facial Emotion Recognition in Parkinson's Disease: An fMRI Investigation. - Albert Wabnegger; Rottraut Ille; Petra Schwingenschuh; Petra Katschnig-Winter; Mariella Kögl-Wallner; Karoline Wenzel; Anne Schienle (PLoS ONE)
Background Findings of behavioral studies on facial emotion recognition in Parkinson's disease (PD) are very heterogeneous. Therefore, the present investigation additionally used functional magnetic resonance imaging (fMRI) in order to compare brain activation during emotion perception between PD patients and healthy controls. Methods and findings We included 17 nonmedicated, nondemented PD patients suffering from mild to moderate symptoms and 22 healthy controls. The participants were shown pictures of facial expressions depicting disgust, fear, sadness, and anger and they answered scales for the assessment of affective traits. The patients did not report lowered intensities for the displayed target emotions, and showed a comparable rating accuracy as the control participants. The questionnaire scores did not differ between patients and controls. The fMRI data showed similar activation in both groups except for a generally stronger recruitment of somatosensory regions in the patients. Conclusions Since somatosensory cortices are involved in the simulation of an observed emotion, which constitutes an important mechanism for emotion recognition, future studies should focus on activation changes within this region during the course of disease.